2010
DOI: 10.5195/jyd.2010.209
|View full text |Cite
|
Sign up to set email alerts
|

Push” and “Pull” A Qualitative Study of Factors that Contribute to Older Youth Leaving the 4-H Program

Abstract: For years, 4-H has struggled with the complex issue of membership retention, especially among older youth. However, little research has been done concerning why 4-H members choose to leave the program. The purpose of this qualitative study was to explore the reasons for leaving 4-H with the ultimate goal of improving retention of older members. Specific objectives of the study were to (a) explore reasons why youth chose not to re-enroll in the program, (b) identify barriers to participation, and (c) determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Competition with other activities is not a new phenomenon to 4-H member retention (Albright & Ferrari, 2010;Astroth, 1985;Harder et al, 2005;Meeks-Baney & Jones, 2013). This is recognized as a challenge by both the volunteer and educator panels.…”
Section: Competing With Other Activities For Youths' Timementioning
confidence: 99%
See 3 more Smart Citations
“…Competition with other activities is not a new phenomenon to 4-H member retention (Albright & Ferrari, 2010;Astroth, 1985;Harder et al, 2005;Meeks-Baney & Jones, 2013). This is recognized as a challenge by both the volunteer and educator panels.…”
Section: Competing With Other Activities For Youths' Timementioning
confidence: 99%
“…This is recognized as a challenge by both the volunteer and educator panels. As youth get older, time conflicts can arise with jobs and other out-of-school organizations such as organized sports (Albright & Ferrari, 2010;Harder et al, 2005). Meeks-Baney and Jones (2013) contend youth want to participate in organizations meeting their needs for affiliation (relationships) and achievement (recognition).…”
Section: Competing With Other Activities For Youths' Timementioning
confidence: 99%
See 2 more Smart Citations
“…Issues of -uninvolved and over-involved‖(Albright, 2010, p. 6) club leaders were mentioned. As previously mentioned, these negative experiences within the 4-H club environment may affect persistence of members Albright's (2010). research also revealed another reason for decreased participation: competition.…”
mentioning
confidence: 62%